Perancangan Interior Bengkel Body Repair Yuspeed di Surabaya dengan konsep “Moving Forward” - Billy Sugihono; martino dwi nugroho; Poppy Firtatwentyna Nilasari (Intra, 2014)
The growing number of cars in Indonesia is getting higher, particularly in big cities like Surabaya, the second largest city in Indonesia. Aesthetic considerations become a major factor in choosing a car. With the rapidly growing amount of cars, the number of car repair services also increased. This is because the car owners always wants their car to be perfect. Therefore, whenever there is minor or major accident, the car owners will try to restore the condition of their car to its initial condition. Yuspeed is one of car repair shops in the city of Surabaya. A company's revenue is influenced by a lot of things, one of which is the presence of good interior design. With a well planned interior design in Yu'Speed, it is expected to provide a good repair services, and also makes visitors feel pampered and comfortable.